The Problem Of The Grammatical Category Of The Chinese Language - Akramdjan Abilevich Karimov (Zien Journals, 2022)
This article is devoted to the category of numbers, one of the topics that has caused many questions in the process of teaching Chinese to students. In other words, languages use certain tools when expressing plural and singular meanings. However, the idea that words in Chinese are more neutral than numbers is common among scholars. At the same time, the same scholars themselves talk about the existence of the plural form in Chinese, and that it is not only morphological, but also lexical and logical (expressed through context). In our view, although words in the lexical form express a certain neutrality with respect to a number, this does not mean that there is no singular or plural, i.e., a category of numbers in the language as a whole. We know this to be a typological feature. This means that if each language represents a certain grammatical category, unlike other languages, it should be considered that it is a typological feature. Needless to say, this grammatical category does not exist at all. We think it is necessary to consider the views of all scientists and draw objective conclusions by comparing them with linguistic phenomena. Therefore, in our opinion, it is possible to talk about the category of numbers in Chinese as well, but it should be approached without interfering with Indo-European standards.
Keywords: isolation; typology; number category; combinations